2021
DOI: 10.3390/su13137433
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable and Global Health Perspective of the Dietary Pattern of French Population during the 1998–2015 Period from INCA Surveys

Abstract: In France, the evolution of dietary pattern relative to sustainability and global health remains insufficiently studied. The objective of this study was to assess dietary changes during 1998–2015 through three generic metrics potentially related to sustainability. Food consumption data were collected from three French National Individual Study of Food Consumption surveys (INCA) for children (0–17 years) and adults (18–79 years) representative of the French population. The consumed foods were converted into pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Recent studies [57,58] reinforced the role of dietary shifts towards less meat consumption in public policy. However, the psychological distance was not a critical preventive factor in food adoption in emerging economies [59,60]. In this sense, the current study extends the previous evidence by applying CLT to food behaviour change decisions.…”
Section: Study Implicationssupporting
confidence: 64%
“…Recent studies [57,58] reinforced the role of dietary shifts towards less meat consumption in public policy. However, the psychological distance was not a critical preventive factor in food adoption in emerging economies [59,60]. In this sense, the current study extends the previous evidence by applying CLT to food behaviour change decisions.…”
Section: Study Implicationssupporting
confidence: 64%
“…Various studies have revealed that the main consumers of UP foods are children and adolescents, with caloric intake from UP foods ranging from 67% in the USA in 2018 in children aged 2-19 years [56] to 45.5% in France by the analysis of data from the INCA3 2014-2015 study (children aged 1-10 years) [57]. In Brazil, the proportion of total UP foods energy consumption was reported as 42.0% ± 8.7 at ages 3-4 years and 47.8% ± 8.9 at ages 6-8 years [58].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that children and adolescents are the main consumers of ultra-processed foods [ 50 , 51 ], with caloric intake mainly from UPFs: 67% in the US in 2018 in 2- to 19-year-olds [ 52 ] and 65.8% in the UK in 4- to 10-year-olds [ 53 ], even in Mediterranean based countries [ 54 ]. In France, analysis of data in the INCA3 study (1- to 10-year-olds; n = 1035) suggests that 45.5% of calories came from UPFs in 2014–2015, which is an increase compared to INCA1 (1998–1999; 42.8%) and INCA2 (2006–2007; 43.2%) [ 55 ]. In its call to action, the European Childhood Obesity Group warned about the negative effects of children consuming large amounts of UPFs and called for restrictions [ 56 ].…”
Section: Discussionmentioning
confidence: 99%